The Measurement of Non-Performing Finance Using the Approaches of Market Segmentation in Islamic Banking - Wahyuni, Nanik; T, Sutrisno; Saraswati, Erwin; Ghofar, Abdul (International Journal of Engineering and Technology, 2019)
Background: Research shows that financial variables are not enough to predict the success of future bank, thus we have to think again about the measurement of non-performing finance to see company’s success. Objective: The objective of this study is to analyze the measurement of non-performing finance to the approaches of market segmentation (product, professional, the image of the bank, and the principles of the bank) at Islamic banks. Result: The result shows that concurrently there is an influence of independent variable into dependent variable;however, the professional variable and image of the bank is not significantly influencing the non-performing finance of Islamic banking. Conclusion: The dominant variable affecting into non-performing finance is a product, so that the variation of the product that is offered by Islamic banks to market or costumer should be taken care. The implementation of the right Islamic principles is also being a costumer’s attention. The upcoming research is advised to concurrently integrate the measurement of financing and non-performing finance to know the complete Islamic banks performing conditions.